1980
DOI: 10.1037/0022-3514.38.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of television commercials on women's self-confidence and independent judgment.

Abstract: This study investigated the impact of television commercials on women's selfconfidence and independence of judgment. Two matched series of commercials served as stimuli. One series consisted of four replicas of current network commercials. The other series consisted of the same four commercials, identical in every respect except that each of the roles in the scenario was portrayed by a person of the opposite sex. Subjects (N = 52 college women) viewed either the traditional or reversed-role series. Those expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Although this seems unlikely, given that even obvious sexism is not always recognized (Hansen & Hansen, 1988;Jennings-Walstedt et al, 1980;L. A. Rudman & Borgida, 1995;Schwarz et al, 1987), research employing different priming techniques and outcome measures is necessary to establish what is being activated by the latent content and whether it is indeed occurring unconsciously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this seems unlikely, given that even obvious sexism is not always recognized (Hansen & Hansen, 1988;Jennings-Walstedt et al, 1980;L. A. Rudman & Borgida, 1995;Schwarz et al, 1987), research employing different priming techniques and outcome measures is necessary to establish what is being activated by the latent content and whether it is indeed occurring unconsciously.…”
Section: Discussionmentioning
confidence: 99%
“…In its review of the literature, the APA (2007) identified implicit, automatic, unconscious processes as mechanisms by which sexist media may have its effects. Similarly, in several studies where stimuli were overtly sexist and demonstrably affected participants, researchers concluded that their participants nevertheless did not recognize the sexism (Hansen & Hansen, 1988;Jennings-Walstedt, Geis, & Brown, 1980;Lavine et al, 1999;L. A. Rudman & Borgida, 1995;Schwarz et al, 1987).…”
mentioning
confidence: 99%
“…Geis and colleagues (Geis, Brown, Jennings, & Porter, 1984) reported that participants who watched reversed-role commericals, compared to women who watched traditional commercials, were more likely to emphasize achievement rather than homemaking in essays speculating about their lives in ten years. Nontraditional commercials, compared to more stereotypical commercials, were also found to increase women's self-confidence and independence of judgment (Jennings, Geis, & Brown, 1980). Similarly, Kilbourne (1990) found that nonstereotypical advertisements affected men's ratings of a female photograph on traits such as leadership and aggressiveness.…”
mentioning
confidence: 94%
“…Several researchers have been interested in the effects of television programs and commercials on sex-role development in children (e.g., Atkin & Miller, 1975;Flerx, Fidler, and Rogers, 1976;Miller and Reeves, 1976;Pingree, 1978). Other researchers have been concerned with the effects of television commercials on women's achievement aspirations, selfconfidence, and independence of judgment (Geis, Brown, Jennings, and Porter, 1984;Jennings, Geis, and Brown, 1980). Generally, these studies have found that when commercials portrayed women as egalitarian sex role models, children changed their attitudes toward women and accepted them in nonstereotypic job roles.…”
mentioning
confidence: 99%